2022
DOI: 10.1002/jcb.30347
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism reprogramming in colorectal cancer

Abstract: The hallmark feature of metabolic reprogramming is now considered to be widespread in many malignancies, including colorectal cancer (CRC). Of the gastrointestinal tumors, CRC is one of the most common with a high metastasis rate and long insidious period. The incidence and mortality of CRC has increased in recent years. Metabolic reprogramming also has a significant role in the development and progression of CRC, especially lipid metabolic reprogramming. Many studies have reported that lipid metabolism reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Hence, changes in FA sources may determine the phospholipid composition of cell membranes and thus indirectly affect membrane function (33,34). Reactivating de novo synthesis of FA is the main pathway for CRC cells to obtain FA (35). In our results, the shared 10 FA we found in CRC cells at different stages were mainly involved in linoleic acid metabolism and carnitine metabolism.…”
Section: Discussionsupporting
confidence: 53%
“…Hence, changes in FA sources may determine the phospholipid composition of cell membranes and thus indirectly affect membrane function (33,34). Reactivating de novo synthesis of FA is the main pathway for CRC cells to obtain FA (35). In our results, the shared 10 FA we found in CRC cells at different stages were mainly involved in linoleic acid metabolism and carnitine metabolism.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, the downregulation of proliferative signaling could reprogram the cell’s lipid usage and lead to lipid storage. Lipid droplets have been shown to accumulate under stress conditions in CRC and can contribute to chemoresistance. , We also aimed to quantitatively compare the metabolites identified with RS (Figure a) with those obtained with LC–MS (Figure b) and specifically represent cell membrane phospholipids (722 cm –1 ), DNA bases (783 cm –1 ), arginine (991 cm –1 ), and triglycerides (1300 cm –1 ) with equivalent representative species from the LC–MS data. We find that for RS and LC–MS, the trends in metabolites for the various sample groups are generally in agreement, which not only shows that these two approaches are complimentary but also highlights the strengths and limitations of each method. RS is a low-cost extraction-free approach that allows rapid measurement of cells at the single cell level capturing heterogeneities in treatment response within individual cells with high sensitivity.…”
Section: Resultsmentioning
confidence: 91%
“…Lipid droplets have been shown to accumulate under stress conditions in CRC and can contribute to chemoresistance. 45,70 We also aimed to quantitatively compare the metabolites identified with RS (Figure 5a) with those obtained with LC−MS (Figure 5b) and specifically represent cell membrane phospholipids (722 cm −1 ), DNA bases (783 cm −1 ), arginine (991 cm −1 ), and triglycerides (1300 cm −1 ) with equivalent representative species from the LC−MS data. 35−39 We find that for RS and LC−MS, the trends in metabolites for the various sample groups are generally in agreement, which not only shows that these two approaches are complimentary but also highlights the strengths and limitations of each method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids have vital physiological functions. In addition to being the main components of cell membranes, they are involved in the synthesis and regulation of biological macromolecules and serve as second messengers and energy reservoirs [ 25 ]. Previous studies indicated that phospholipids levels increase in CRC tissue, possibly due to increased synthesis of plasma membranes in rapidly proliferating cancer cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%